743Determinants of childhood mortality sex ratios in low- and middle-income countries. (2nd September 2021) - Costa, Janaina Calu; Victora, Cesar
Abstract: Background: Child mortality sex ratios may reflect community preferences and gender discrimination in health care. We assessed differences between observed and expected sex ratios of under-five mortality and their association with contextual factors. Methods: Full birth histories from Demographic and Health Surveys and Multiple Indicator Cluster Surveys (2010–2018) in 77 countries were used to estimate under-five mortality sex ratios (male-to-female). Expected sex ratios and their residuals (difference of observed from expected) were derived from a fractional polynomial model, adjusted for overall mortality. Higher male-to-female residuals indicate lower likelihood of discrimination against girls. The same approach was used for 720 subnational regions from 75 countries. Associations between residuals and national gender and development indices, and with survey-derived child health care indicators were tested using Spearman's correlation. Results: Greater positive residuals were found in countries with higher Gross National Product per capita (rho=0.26), women older age at first marriage (rho=0.36), Human Development Index (rho = 0.23), and the Women, Peace and Security Index (rho=0.25). The Gender Inequality Index, which indicates less discrimination among women, was inversely correlated with the residuals (rho=-0.30). None of the survey-based indicators of gender bias in health care were significantly associated with the residuals, either at national or subnational levels. Conclusion: Contextual variables measured at country level are associated with the sex ratio of under-five mortality. Key messages: In more developed societies there is less evidence of gender bias in child deaths.